1997
DOI: 10.1192/pb.21.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric emergencies: assessing parents of dependent children

Abstract: Frameworks within which services are delivered to people with mental health problems neglect the specific needs of those with dependent children. These children have been identified as having risks to their development and well-being. A system of monitoring social assessments of mental health crisis is used to examine the characteristics of parents assessed in seven Local Authorities across 3 calendar years. Parents of dependent children are underrepresented, and are more likely to be women and to suffer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Increasing numbers of Mental Health Service users are parents, many of whom are children's primary caregivers (Hatfield, Webster, & Mohhamad, 1997;McGrath et al, 1999;White, Nicholson, & Fisher, 1995). Globally, approximately 60% of women with enduring mental health difficulties have children under 16 years of age (Reder, McClure, and Jolley, 2000, p. 175); and within the United Kingdom, research by Gillam, Crofts, Fadden, and Corbett (2003), p. 34) identified that between 25% and 49% of Community Mental Health (CMH) Team service users were parents of dependent children.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of Mental Health Service users are parents, many of whom are children's primary caregivers (Hatfield, Webster, & Mohhamad, 1997;McGrath et al, 1999;White, Nicholson, & Fisher, 1995). Globally, approximately 60% of women with enduring mental health difficulties have children under 16 years of age (Reder, McClure, and Jolley, 2000, p. 175); and within the United Kingdom, research by Gillam, Crofts, Fadden, and Corbett (2003), p. 34) identified that between 25% and 49% of Community Mental Health (CMH) Team service users were parents of dependent children.…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known about the care arrangements for children when women are taken into hospital, despite the Department of Health highlighting the ' significance and effect of parental mental health problems on children ' (Department of Health, 1997). Hatfield, Webster and Mohamad (1997) report that just over half of all psychiatric admission episodes involve women (Department of Health, 1995) but information on parental status does not seem to be routinely recorded (Stormont et al, 1997). Once psychiatric patients are recognised as parents and part of a family unit, it is important that the impact of their situation is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Women with psychotic disorders are more likely than men with psychosis to be involved in child care. A study of 551 Mental Health Act assessments involving parents living with dependent children found that 72% involved women (Hatfield et al, 1997).…”
Section: Do Patients With Psychotic Disorders Have Children?mentioning
confidence: 99%